Comparison of shape memory polymer foam versus bare metal coil treatments in an in vivo porcine sidewall aneurysm model. Issue 7 (3rd June 2016) - Horn, John; Hwang, Wonjun; Jessen, Staci L.; Keller, Brandis K.; Miller, Matthew W.; Tuzun, Egemen; Hartman, Jonathan; Clubb, Fred J.; Maitland, Duncan J.
Abstract: The endovascular delivery of platinum alloy bare metal coils has been widely adapted to treat intracranial aneurysms. Despite the widespread clinical use of this technique, numerous suboptimal outcomes are possible. These may include chronic inflammation, low volume filling, coil compaction, and recanalization, all of which can lead to aneurysm recurrence, need for retreatment, and/or potential rupture. This study evaluates a treatment alternative in which polyurethane shape memory polymer (SMP) foam is used as an embolic aneurysm filler. The performance of this treatment method was compared to that of bare metal coils in a head‐to‐head in vivo study utilizing a porcine vein pouch aneurysm model. After 90 and 180 days post‐treatment, gross and histological observations were used to assess aneurysm healing. At 90 days, the foam‐treated aneurysms were at an advanced stage of healing compared to the coil‐treated aneurysms and showed no signs of chronic inflammation. At 180 days, the foam‐treated aneurysms exhibited an 89–93% reduction in cross‐sectional area; whereas coiled aneurysms displayed an 18–34% area reduction. The superior healing in the foam‐treated aneurysms at earlier stages suggests that SMP foam may be a viable alternative to current treatment methods. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 1892–1905, 2017.